A comparative study of different types of connective tissue-associated interstitial lung disease - Xinyi Li; Hongmei Zhang; Xiaoyue Zhang; Guokun Wang; Xue Zhao; Jinling Zhang (BMC Medical Imaging)
Abstract Introduction Interstitial lung disease (ILD) is an important pulmonary complication of connective tissue disease (CTD). This study aimed to analyze high-resolution computed tomography (HRCT) manifestations of different connective tissue-associated interstitial lung diseases (CTD-ILDs) to improve diagnostic accuracy. Method This study retrospectively included 99 patients diagnosed with CTD-ILD between September 2017 and July 2024. Visual assessment and quantitative CT analysis were used to evaluate HRCT manifestations. Results The age of the rheumatoid arthritis (RA) group was significantly greater than that of the polymyositis/dermatomyositis (PM/DM) and systemic sclerosis (SSc) groups (p = 0.025 and p = 0.02), with a mean age of 64.4 ± 10 years. The most common HRCT pattern of CTD-ILD was nonspecific interstitial pneumonia (NSIP) (p = 0.008); the adjusted residual > 1.96, usual interstitial pneumonia (UIP) was most frequently observed in the RA group, organizing pneumonia (OP) was most commonly observed in the PM/DM group, and lymphocytic interstitial pneumonia (LIP) was observed only in the primary Sjögren’s syndrome (pSjS) group. The CTD-ILD groups exhibited significant differences in bronchiectasis (χ2 = 11.256, p = 0.0022), esophageal dilatation (χ2 = 33.923, p < 0.001), mediastinal lymph node enlargement (χ2 = 10.103, p = 0.041), and thin-walled cysts (χ2 = 14.081, p = 0.006). Adjusted residual > 1.96, esophageal dilatation was commonly observed in the SSc group; bronchiectasis was more common in the RA group; mediastinal lymph node was more common in the pSjS group. Statistically significant differences in the predominance of different CTD-ILDs (χ2 = 20.814, p = 0.0046). The PM/DM group exhibited significant consolidation and reticulation. The extensive honeycombing was present in the RA-ILD group (p = 0.044). Based on logistic binary regression analysis, bronchial dilatation (odds ratio: 4.506, p = 0.005) and extensive honeycombing (odds ratio: 1.282, p = 0.021) were significant predictors of RA-ILD, while lymph node enlargement (odds ratio: 3.314, p = 0.039) and thin-walled cysts (odds ratio: 6.278, p = 0.001) were predictors of pSjS-ILD. Conclusion Different types of CTD-ILD have characteristic HRCT manifestations. Clinical trial number As this study involved standard clinical procedures and assessments without an experimental treatment protocol, it did not require registration with a public clinical trials registry.